TARANTULA SEBAGAI STRUKTUR BENTUK PENCIPTAAN KURSI TERAS - Ahmad Solikin; Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2019)
Designers are required to be able to develop themselves in creating a product that is able to attract public interest. People need a place to rest and relax, one of the facilities is to relax using a patio chair. Terrace chairs as a relaxing facility need a comfortable and functional design, in this case the Tarantula as a structure for creating patio chairs that prioritizes function and aesthetic value The purpose of making the design is to create a patio chair with a tarantula shape as a form structure to create a terrace chair creatively and innovatively. Patio chairs are sitting facilities for a means of relaxing or relaxing on the terrace.The tarantula is not taken completely but only takes its main characteristics and distorts the original form but does not eliminate the character of the tarantula itself.